2022
DOI: 10.3390/su14138142
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Behaviors Analysis of Sideswipe Collision on Urban Expressways Based on Bayesian Network

Abstract: The causes of crashes on urban expressways are mostly related to the unsafe behaviors of drivers before the crash. This study focuses on sideswipe collisions on urban expressways. Through real and visual crash data, 17 unsafe behaviors were identified for the analysis of sideswipe collisions on an urban expressway. The chains of high-risk and unsafe behaviors were then revealed to investigate the relationship between drivers’ unsafe behaviors and sideswipe collisions. A Bayesian network diagram of unsafe behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…A Bayesian network (BN) represents causal features as a network (weighted graph) by means of a directed graph and then predicts the likelihood of complex and uncertain events by performing probabilistic reasoning. Based on the information accumulated so far, the probability of occurrence of each scenario can be calculated and based on the path of occurrence, thus quantitatively representing the probability of occurrence where causality exists due to complex paths [38,39].…”
Section: Incident Cause Prediction Based On Bayesian Networkmentioning
confidence: 99%
“…A Bayesian network (BN) represents causal features as a network (weighted graph) by means of a directed graph and then predicts the likelihood of complex and uncertain events by performing probabilistic reasoning. Based on the information accumulated so far, the probability of occurrence of each scenario can be calculated and based on the path of occurrence, thus quantitatively representing the probability of occurrence where causality exists due to complex paths [38,39].…”
Section: Incident Cause Prediction Based On Bayesian Networkmentioning
confidence: 99%
“…The number of rear-end collisions and side-swipe collisions accounts for about 4% of road traffic accidents in Queensland, Australia [3]; 4.9% of all 2015 road traffic accidents were caused by overtaking and improper lane changing in China [4]; and nearly 5% of all road traffic accidents and 7% of all fatalities in such accidents are caused by improper merging or lane-changing operations in the United States [5]. During the process of lane changing, the poor perception and judgment ability or improper operation of the driver may lead to rear-end collisions and side-swipe collisions more easily [6,7]. Studies have shown that nearly half of drivers fail to use turn signals when changing lanes [8,9].…”
Section: Introductionmentioning
confidence: 99%